The Moderating Role of Government Regulations in the Influence of Competency of Prospective Indonesian Migrant Workers on Destination Country Placement - Sastra, I Gde Leo; Sihombing, Irene Hanna; Utama, I Putu (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
There is a correlation between the increase in prospective Indonesian migrant workers (PMIs) and the increase in employment law violations. Non-procedural PMIs force themselves on migrant workers without proper permission, violating legalities such as incomplete documents and legal provisions, potentially leading to legal problems. Non-procedural PMIs also tend not to go through the placement selection process with a credible agency. The study aims to examine the role of government regulation in moderating the influence of competence on PMI candidate recruitment. The research population consists of Indonesian migrant workers' distributor agencies spread across nine districts and cities in Bali province. The research sample comprises 10 agencies and 10 recruiters who recruited during the years 2021 and 2022 as candidate migrants to 117 placement companies. Data collection for competence variables, government regulations, and placement using questionnaires that have passed validity and reliability tests is a good measurement scale. We analyzed the research data using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, aided by SMART-PLS software, to examine the direct impact of competence on placement, the influence of government regulations on placement, and the moderating effect of governmental regulations on the impact of competence on placement. This study showed that (1) competence had a positive and significant effect on placement, which was backed up by strong empirical data; (2) government regulations also had a positive and significant effect on placement, which was backed up by empire data; and (3) the way that government regulations moderated the relationship between competence and placement was hindering.